Explaining the income-distribution puzzle in happiness research: Theory and evidence - Barbara Dluhosch; Daniel Horgos; Klaus W. Zimmermann (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2012)
The nexus between income and happiness is very much disputed. Many cross-sectional studies see a positive relationship, most longitudinal studies don't. Starting from the fact that the theoretical basis in happiness research has been comparatively weak, we develop a model that identifies distributional consequences of unemployment with their importance conditional per-capita income as at the heart of the matter. Our theory is backed by empirical evidence on OECD data: in low-income countries, well-being significantly depends on income, in highincome countries on the unemployment-related Gini. Insofar, our findings establish the income-satiation hypothesis of longitudinal studies also in cross-sectional perspective.
urn:nbn:de:gbv:705-opus-29815
Keywords: D60; I31; J60; 330; Happiness; Welfare Economics; Income Distribution; Unemployment